Study on High Comfort and Low Energy Consumption Community Design in China. Issue 3 (1st September 2015) - Jinxiu, WU; Meiying, Zhang; Lin, Zhao
Abstract : High comfort and low energy consumption communities have become an important topic for community planning & design in China. Considering the special situation in China, the meaning of high comfort and low energy consumption communities lies in three aspects: making utmost use of natural climatic conditions, providing enjoyable indoor and outdoor living environments in circumstances of high-rise and high-density development, and holistic design of adjacent dwelling units to provide utmost flexibility. This paper uses design proposals for two real projects in two different cities in China - one in Yixing in South China and another one in Harbin in north China - as examples of how to design high comfort and low energy consumption communities by following local climatological factors and by respecting occupants' needs in the long run. This paper shows that such communities can be planned in two steps, with special attention to the local climate. First, climatically responsive site planning determines building layout, height of each part, and also the design of open spaces. Second, detailed planning & design addresses the disadvantages of the site, improving space quality. Following local climatological conditions is also one of the key issues in housing design for high comfort & low energy consumption communities. In the housing design of the Harbin project, besides consideration to climate, special attention was also given to flexible/variable dwelling unit design according to occupants' long-term needs. The "1+1 mode" is put forward to provide utmost flexibility for families with 3 generations for their current and future lives.